Pengaruh Kombinasi PMK dengan Media Tanam dan Konsentrasi AB Mix terhadap Pertumbuhan Bibit Tanaman Alpukat (Persea americana Mill.) - Ath Thariq, Riyano; Nur, M. (UIR PRESS, 2026)
The aim of the study was to determine the effect of interaction between red-yellow podzolic (RYP) soil and the combination of RYP with planting media and AB Mix nutrients on the growth of avocado seedlings in the field (Persea americana Mill.). This research was carried out at the Experimental Garden of the Faculty of Agriculture, Riau Islamic University. This research was conducted for 4 months, starting from August to November 2022. This research was conducted using a Completely Randomized Factorial Design which consisted of two factors, the first factor was various types of planting media consisting of 4 treatment levels and the second factor was the provision of various AB Mix nutrients consisting of 4 treatment levels. Result showed that interaction of various types of planting media and AB Mix Nutrients is significant for all observation parameters. The best treatment is PMK 50% + Rice Husk 50% and 2500 ppm. The main effect of various types of planting media is significant on all observation parameters, where the best treatment is PMK 50% + Rice Husk 50%. The main effect of AB Mix Nutrition is significant for all observation parameters, where the best treatment is 2500 ppm.